Subtraction dual-wavelength for enhanced transmission performance of free-space optical communication over turbulence effect - Abdul Rahman, Kram; Kwang Thai, C.A.; Tamrin, K. F.; Sahari, S.K. (John Wiley & Sons, 2021)
Performance of a free-space optical communication system is influenced by atmospheric turbulence which degrades signal transmission quality. A gamma–gamma channel model is employed to characterise this turbulence under weak-to-strong conditions. The proposed dual diffuser modulation using subtraction dual-wavelength concept is combined with a phase screen diffuser to improve signal transmission. Its performances are compared with conventional intensity modulationdirect detection on off keying and partial coherent beam on off keying techniques. In comparison, results show that the dual diffuser modulation demonstrates superior performances in both received power and bit rate transmission under different turbulence conditions.